Ferroelectric and dielectric properties of lanthanum-modified bismuth titanate thin films obtained by the polymeric precursor method - Simoes, A. Z.; Gonzalez, AHM; Riccardi, C. S.; Souza, E. C.; Moura, F.; Zaghete, M. A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2004)
Lanthanum-modified bismuth titanate, Bi4-xLaxTi3O12 (BLT), thin films with a La concentration of 0.75 was grown on Pt/Ti/SiO2/Si substrates by using the polymeric precursor solution and spin-coating method. The scanning electron microscopy (SEM) showed rounded grains, which is not typical for these system. The BLT films showed well-saturated polarization-electric field curve which 2P(r) = 41.4 muC/cm(2) and V-c = 0.99 V. The capacitance dependence on the voltage is strongly nonlinear, confirming the ferroelectric properties of the film resulting from the domains switching. These properties make BLT a promising material for FERAM applications.
Keywords: bismuth lanthanum titanate; FERAM; thin film